Analisis Kesulitan Belajar Siswa pada Materi Geometri di Sekolah Dasar: Studi Literatur - Nova Sandra Prasetianingrum; Elvi Muawwanah; Hana Novita Nuraini; Fauzan Anargya; I Emas Mohammad Said; Dea Anata Wijaya Tanjung (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to analyze elementary school students' learning difficulties in geometry and to identify their causes and alternative instructional strategies for teachers. A descriptive qualitative literature review was employed. Data were obtained by reviewing scientific articles and academic sources relevant to geometry learning, plane and solid figures, and mathematics learning difficulties at the elementary level. The data were analyzed through identification, reduction, classification, and synthesis of findings. The review indicates that students experience difficulties in understanding concepts, distinguishing properties of geometric figures, performing spatial visualization, applying perimeter, area, and volume formulas, and solving geometry word problems. These difficulties are influenced by internal factors, including weak conceptual understanding, limited prerequisite mathematical skills, low motivation, and lack of accuracy, as well as external factors, including less varied teaching methods, limited use of concrete media, and insufficient contextual learning experiences. Therefore, elementary geometry instruction should be concrete, gradual, visual, and centered on student activities.